Melodic Structure, Harmony, and Dissonance in Jaya Suprana’s Piano Work Dedemit - Kamaludin Galingging; Hendrik L Simanjuntak; Kartini R Manalu (Melayu Arts and Performance Journal, 2026)
This study examines a solo piano work by a second-generation Indonesian composer, following Amir Pasaribu and Mochtar Embut. Jaya Suprana is a pianist and composer, and is widely recognized as an Indonesian cultural figure. As the second generation in the context of Indonesian piano composers, Jaya Suprana has provided a milestone in expanding the concept of musical composition and introducing it to the international world. Through various musical performances, concerts, and recitals, Jaya Suprana's piano compositions have graced numerous venues both domestically and internationally. What's fascinating about Jaya Suprana's compositional concept is its difficult-to-interpret element of "simplicity." This composition concept seems to be a personification that is attached to Jaya Suprana and continues to this day, even though many other composers also worked in a similar period. The urgency of this research is to find the composer's mindset in the aspect of 'simplicity' which is difficult for players to interpret. This research is part of the future development of composition concepts and will serve as learning material in higher education, specifically in the concentration of music composition and presentation. The method chosen for this research is a qualitative descriptive method with a musicological approach